No incremental benefit of multisite atrial pacing compared with right atrial pacing in patients with drug refractory paroxysmal atrial fibrillation. Issue 1 (1st January 2001) - Levy, T; Walker, S; Rex, S; Rochelle, J; Paul, V
Abstract : OBJECTIVE: To evaluate the incremental antifibrillatory effect of multisite atrial pacing compared with right atrial pacing in patients with drug refractory paroxysmal atrial fibrillation paced for arrhythmia prevention alone. METHODS: In 20 of these patients (mean (SD) age 64 (8) years; 14 female, six male), a single blinded randomised crossover study was performed to investigate the incremental benefit of one month of multisite atrial pacing compared with one month of right atrial pacing. Outcomes included the number of episodes of paroxysmal atrial fibrillation, their total duration obtained from pacemaker Holter memory, and quality of life using a cardiac specific questionnaire (the modified Karolinska questionnaire). RESULTS: Comparing right atrial with multisite atrial pacing, there was no significant change in either the number of paroxysmal atrial fibrillation episodes (mean (SD): right atrial pacing 77 (98) episodes v multisite pacing 52 (78) episodes, NS) or their total duration (right atrial, 4.8 (5.4) days v multisite, 6.3 (9.8) days, NS). Quality of life scores compared with baseline status were equally improved by either pacing strategy (mean percentage improvement: right atrial, 38%, p = 0.003; multisite, 44%, p = 0.003). There was no significant difference in life scores comparing the two pacing modes. CONCLUSIONS: Multisite atrial pacing has no incremental antiarrhythmic effect compared with right atrial pacing in patients paced for drug refractory paroxysmal atrial fibrillation. Quality of life is equally improved with either pacing strategy, with no differences between them.